Panel | Marquetry Panel with Arcade Decoration
Probably side panel from cenotaph; like those found in 'Ain al-Sira cemetery in Egypt. Incorporates design elements from Late Antique / Mediterranean and Sasanian cultures. Wood (fig), mosaic with bone and four different types of wood